Hepatitis C virus core protein impairs metabolic disorder of liver cell via HOTAIR-Sirt1 signalling. Issue 3 (20th May 2016) - Li, Zhi-qin; Gu, Xin-yu; Hu, Jin-xing; Ping, Yu; Li, Hua; Yan, Jing-ya; Li, Juan; Sun, Ran; Yu, Zu-jing; Zhang, Yi
Abstract : It has been suggested that Hepatitis C virus (HCV) core protein is associated with metabolic disorders of liver cell. However, the precise mechanism is still unclear. The aim of the present study was to explore the impact of HCV core protein on hepatocyte metabolism by HepG2 and the possible involvement of long non-coding (lnc) RNAs in this process. The effect of HCV core protein on lncRNAs expression was examined with quantitative RT-PCR (qRT-PCR). Manipulation of HVC core protein and lncRNA HOTAIR was to evaluate the role of interaction between them on cell metabolism-related gene expression and cellular metabolism. The potential downstream Sirt1 signal was examined by western blotting and qRT-PCR. Our data suggested that suppression of HOTAIR abrogates HCV core protein-induced reduction in Sirt1 and differential expression of glucose- and lipid-metabolism-related genes. Also it benefits for metabolic homoeostasis of hepatocyte indicated by restoration of cellular reactive oxygen species (ROS) level and NAD/NADH ratio. By manipulation of HOTAIR, we concluded that HOTAIR negatively regulates Sirt1 expression through affecting its promotor methylation. Moreover, overexpression of Sirt1 reverses pcDNA-HOTAIR-induced glucose- and lipid-metabolism-related gene expression. Our study suggests that HCV core protein causes dysfunction of glucose and lipid metabolism in liver cells through HOTAIR-Sirt1 signalling pathway.